Design and Analysis of Hexagonal Fractal Antenna for UWB Application (International Journal of Engineering and Computer Science, 2015)
A fractal antenna having the shape of hexagonal for UWB application is designed. The frequency band is considered from 3 to 10.6 GHz. This antenna is designed on a dielectric FR4 epoxy substrate of dimension (50mm X 40mm) permittivity €r =4.4 and height = 1.6mm and it is fed by a 50 ohm microstrip line. With this structure the return loss less than -10dB, VSWR, radiation pattern get improved. The proposed antenna is simulated by using the HFSS software. The simulated results are in good agreement with experimental results.